(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
This study aimed to assess the influence of pedagogical activities on the behavior of hospitalized children and their accompanying adults. The study was carried out at the Pediatrics Center of a hospital in a medium-size city in São Paulo State, Brazil. Eighty-seven children of both genre, in addition to their accompanying adults, participated in the study. The research comprised the following phases: (1) observations of behavior of child-accompanying adult dyads before intervention; (2) interviews to characterize participants; (3) observations of the behavior of child-accompanying adult dyads during intervention; and (4) final individual interviews with children and accompanying adults, when they were asked: “What did you think of the activities?”. Results indicate the positive influence of pedagogical activities on the behavior of children and accompanying adults, with significant repercussion on the former’s physical, mental and emotional health as well as on the hospital environment and interactions with its employees.